Pengaruh Pengawasan Kepala Sekolah Terhadap Efektivitas Pelaksanaan Program Indonesia Pintar (PIP) Di Smpn 1 Warungkiara Kabupaten Sukabumi. - Dede Riansyah (STISIP Widyapuri Mandiri Sukabumi, 2023)
KKM or Student Work Lecture is one of the campus programs where students carry out community service with an interdisciplinary approach and the length of time for implementation is determined by the campus. The field of education is of particular concern to the author because education, whether we realize it or not, is a need for every human being because no human being is born with knowledge. Of the various problems in education, learning motivation is of particular concern to be addressed, especially learning motivation in elementary school children. Learning motivation has a very important role in learning, both in the learning process and in the results obtained in learning. The activities themselves are carried out at the KKM Command Post, namely Post IV which is located at Jalan Kampung Cikupa, Rt 03/Rw 03 Cikelat Village, Cisolok District, Sukabumi Regency. The method used is awareness/increasing understanding of a problem. There are several factors that cause low learning motivation in students, especially elementary school students, including: Lack of guidance from parents, Dislike of certain subjects, Limited learning support media. Tutoring is not only for students at school, but tutoring is also carried out in other fields such as reading and writing the Koran, memorizing prayers, and others. In tutoring activities, there are perceived obstacles, namely unstable student concentration levels and a variety of different learning methods because students come from different schools and at different levels. In the process of motivating students, the activities carried out in tutoring are as follows: Adapting learning to the participants/students, Providing encouragement to students, Giving gifts or morning praise to students, Creating a fun atmosphere such as exercising, playing games and drawing.